Comparative Effectiveness of Bone Grafting Using Xenograft Freeze-Dried Cortical Bovine, Allograft Freeze-Dried Cortical New Zealand White Rabbit, Xenograft Hydroxyapatite Bovine, and Xenograft Demineralized Bone Matrix Bovine in Bone Defect of Femoral Diaphysis of White Rabbit: Experimental Study In Vivo - Ferdiansyah Mahyudin; Dwikora Novembri Utomo; Heri Suroto; Tri Wahyu Martanto; Mouli Edward; Imelda Lumban Gaol (International Journal of Biomaterials)
Autogenous bone graft is gold standard in treating bone defects, but it might have difficulty in corporation and rejection reaction. This study is to compare the effectiveness among freeze-dried xenograft, freeze-dried allograft, hydroxyapatite xenograft, and demineralized bone matrix xenograft as bone graft to fill bone defect in femoral diaphysis of white rabbit. Thirty male New Zealand white rabbits were distributed into five groups. Bone defect was filled correspondingly with xenograft freeze-dried cortical bovine, allograft freeze-dried cortical New Zealand white rabbit, xenograft hydroxyapatite bovine, and xenograft demineralized bone matrix bovine. No graft was used in control group. VEGF, osteoblast, and woven bone were higher in allograft freeze-dried cortical New Zealand white rabbit (mean 5.6625 (p<0.05)) and xenograft demineralized bone matrix bovine (mean 5.2475 (p<0.05)) with calcification of woven bone was already seen in week 2 in the latter group. There was a decrease of woven bone (mean 4.685 (p<0.05)) fibrous tissue (mean 41.07 (p<0.05)) in xenograft demineralized bone matrix bovine. The Immunoglobulin-G was elevated in control and all study groups but not significantly (p=0.07855). Bone healing process in xenograft demineralized bone matrix bovine is more effective than in xenograft hydroxyapatite bovine, allograft freeze-dried New Zealand white rabbit, xenograft freeze-dried cortical bovine, and control.